Superparamagnetic Bifunctional Bisphosphonates Nanoparticles: A Potential MRI Contrast Agent for Osteoporosis Therapy and Diagnostic. (23rd May 2010) - Lalatonne, Y.; Monteil, M.; Jouni, H.; Serfaty, J. M.; Sainte-Catherine, O.; Lièvre, N.; Kusmia, S.; Weinmann, P.; Lecouvey, M.; Motte, L.
Abstract : A bone targeting nanosystem is reported here which combined magnetic contrast agent for Magnetic Resonance Imaging (MRI) and a therapeutic agent (bisphosphonates) into one drug delivery system. This new targeting nanoplatform consists of superparamagneticγ Fe 2 O 3 nanoparticles conjugated to 1, 5-dihydroxy-1, 5, 5-tris-phosphono-pentyl-phosphonic acid (di-HMBPs) molecules with a bisphosphonate function at the outer of the nanoparticle surface for bone targeting. The as-synthesized nanoparticles were evaluated as a specific MRI contrast agent by adsorption study onto hydroxyapatite and MRI measurment. The strong adsorption of the bisphosphonates nanoparticles to hydroxyapatite and their use as MRIT 2 ∗ contrast agent were demonstrated. Cellular tests performed on human osteosarcoma cells (MG63) show thatγ Fe 2 O 3 @di-HMBP hybrid nanomaterial has no citoxity effect in cell viability and may act as a diagnostic and therapeutic system.